Forensic Analysis of Wearable Devices: Privacy, Cyber Security, and Legal Challenges in Digital Forensics - S.Thangavel,; Dr. Muruganantham B,; Dr.N.Kala,; Premanand Narasimhan, (International Journal of Scientific Research in Science and Technology, 2024)
A concise summary of the research scope, significance, and key objectives, highlighting the increasing ubiquity of wearable devices and their potential as sources of digital evidence. Emphasize the challenges in privacy, security, and forensic analysis and propose contributions to forensic methodologies.